The Role of Mobile Health (mHealth) in Enhancing Healthcare Delivery in Remote Areas: A Systematic Review - Alotaibi, Muhammad Obaid Mubarak (Journal of medical and pharmaceutical sciences, 2025)
Access to quality healthcare remains a critical challenge in remote and underserved areas, where geographical isolation, limited resources, and a shortage of skilled healthcare professionals contribute to health disparities (World Health Organization [WHO], 2021). Mobile health (mHealth), the use of mobile technologies for health services, has been proposed as a solution to bridge these gaps (Kallander et al., 2013). This systematic review synthesizes evidence from studies published between 2010 and 2024 to evaluate the effectiveness, challenges, and facilitators of mHealth in remote healthcare delivery. Findings indicate that mHealth interventions, including SMS reminders, teleconsultations, and mobile applications, have improved healthcare access, maternal and child health outcomes, chronic disease management, and disease surveillance (Feroz et al., 2020; Okeke et al., 2022). However, barriers such as poor digital literacy, limited infrastructure, and cultural resistance persist (Alami et al., 2020; Smith et al., 2023). The review underscores the need for integrated policies, community engagement, and capacity building to optimize the potential of mHealth in reducing healthcare inequities.